Genetics of spontaneous cervical and coronary artery dissections - Isabel Rada; Juan Francisco Calderón; Gonzalo Martínez; Paula Muñoz Venturelli; Paula Muñoz Venturelli (Frontiers Media S.A., 2023)
ObjectivesSpontaneous cervical artery dissections (SCeAD) and coronary artery dissections (SCoAD) are major causes of neurovascular and cardiovascular morbidity in young adults. Although multiple aspects of their etiology are still unknown, most consensuses are focused on the presence of constitutional genetic aspects and environmental triggers. Since recent evidence of genetic contribution points to a possible overlap between these conditions, we aimed to describe current information on SCeAD and SCoAD genetics and their potential shared pathological aspects.Materials and methodsA narrative review is presented. Publications in English and Spanish were queried using database search. The articles were evaluated by one team member in terms of inclusion criteria. After collecting, the articles were categorized based on scientific content.ResultsGiven that patients with SCeAD and SCoAD rarely present connective tissue disorders, other genetic loci are probably responsible for the increased susceptibility in some individuals. The common variant rs9349379 at PHACTR1 gene is associated with predisposition to pathologies of the arterial wall, likely mediated by variations in Endothelin-1 (ET-1) levels. The risk of arterial dissection may be increased for those who carry the rs9349379(A) allele, associated with lower expression levels of ET-1; however, the local effect of this vasomotor imbalance remains unclear. Sex differences seen in SCeAD and SCoAD support a role for sex hormones that could modulate risk, tilting the delicate balance and forcing vasodilator actions to prevail over vasoconstriction due to a reduction in ET-1 expression.ConclusionsNew evidence points to a common gene variation that could explain dissection in both the cervical and coronary vasculatures. To further confirm the risk conferred by the rs9349379 variant, genome wide association studies are warranted, hopefully in larger and ethnically diverse populations.